2013
DOI: 10.1161/circimaging.113.000690
|View full text |Cite
|
Sign up to set email alerts
|

Size Matters! Impact of Age, Sex, Height, and Weight on the Normal Heart Size

Abstract: Background-Therapeutic decisions in cardiology are determined frequently by cardiac chamber size. To decide whether cardiac dimensions are still in the normal range, reliable reference values are needed. However, published reference values mostly refer to historical cohorts using motion-mode measurements and have not been adjusted for sex or age. The impact of body size was only vaguely addressed. The importance of such adjustments is illustrated by studies, which show that smaller individuals and women are at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 36 publications
(69 reference statements)
9
57
2
4
Order By: Relevance
“…However, most subjects of this study were younger than 50 years of age. This finding is confirmed by other recent studies [30,32] which showed a significant positive impact of age on RV size. However, other studies showed no effect of age on RV area [20,28], while D'Oronzio et al [22] observed a weak negative correlation with age.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, most subjects of this study were younger than 50 years of age. This finding is confirmed by other recent studies [30,32] which showed a significant positive impact of age on RV size. However, other studies showed no effect of age on RV area [20,28], while D'Oronzio et al [22] observed a weak negative correlation with age.…”
Section: Discussionsupporting
confidence: 91%
“…If we consider the mean ± 2 SD of our pooled data (prospective study + data from the meta-analysis), we identified 20.5 cm 2 in females and 25 cm 2 in males as the upper limit of reference ranges for healthy adult European/Americans, and 19 and 24 cm 2 in healthy Asian females and males, respectively. Very similar reference ranges have recently been seen in other large studies [30,32] that did not analyse ethnic differences. The high upper limits of reference ranges result from the high SDs and reflect the large variability of RV area when assessed by echocardiography.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Pregnant or lactating women, athletes, and subjects addicted to alcohol were also excluded by a few authors (15,16,60), and some studies also evaluated smoking (15,21,38,82), anaemia and fever (15,16) as exclusion criteria. However, in some studies (15,19,38,43,52,54,63,82), inclusion criteria were well defined, in other sufficiently explained (20,21,24,30,50,52,61,67,70,74,76), while in few works the criteria were more generic (23,24,26,58,59,69,73).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Cardiac dimensions are significantly affected by age, sex, height, and weight [1]. This raises the question if some of the characteristic sounds generated by the heart are also correlated with these parameters.…”
Section: Introductionmentioning
confidence: 99%